Penerapan Algoritma Fisher Yates untuk Pengacakan Soal Pada Sistem Ujian Kompetisi Wartawan - Tri Sugihartono; Rendy Rian Chrisna Putra (Fakultas Teknik Universitas Hamzanwadi, 2021)
Procedures from the company to provide competency certification for and as official evidence that the news from the journalist is credible. In the practice of implementing the Competency Test, cheating is still found during the exam, various ways / forms of cheating that occur include cooperation between journalists (test participants). These problems are overcome by integrating the competency test system, using mobile technology and web applications that have been integrated so that they are more accessible. The Fisher Yates shuffle algorithm functions as a randomization of exam questions. Each test taker always has different exam questions, both from the numbering of questions and the order of answer choices. With the implementation of the Fisher Yates Suffle Algorithm, it can reduce acts of fraud or dishonesty by journalists. In addition, with the application of the Fisher Yates shuffle algorithm, it can make it easier for agencies to provide competent employee competencies. The results of the randomization test on the first 3 questions that appeared to the respondents resulted in the conclusion that the Fisher-Yates shuffle algorithm had a 100% success rate in randomizing the order of questions that were displayed to respondents.